Fractional Calculus for Type 2 Interval-Valued Functions - Mostafijur Rahaman; Dimplekumar Chalishajar; Kamal Hossain Gazi; Shariful Alam; Soheil Salahshour; Sankar Prasad Mondal (Fractal and Fractional)
This paper presents a contemporary introduction of fractional calculus for Type 2 interval-valued functions. Type 2 interval uncertainty involves interval uncertainty with the goal of more assembled perception with reference to impreciseness. In this paper, a Riemann–Liouville fractional-order integral is constructed in Type 2 interval delineated vague encompassment. The exploration of fractional calculus is continued with the manifestation of Riemann–Liouville and Caputo fractional derivatives in the cited phenomenon. In addition, Type 2 interval Laplace transformation is proposed in this text. Conclusively, a mathematical model regarding economic lot maintenance is analyzed as a conceivable implementation of this theoretical advancement.